2017
DOI: 10.3389/fncel.2017.00198
|View full text |Cite|
|
Sign up to set email alerts
|

Synaptic Ribbon Active Zones in Cone Photoreceptors Operate Independently from One Another

Abstract: Cone photoreceptors depolarize in darkness to release glutamate-laden synaptic vesicles. Essential to release is the synaptic ribbon, a structure that helps organize active zones by clustering vesicles near proteins that mediate exocytosis, including voltage-gated Ca2+ channels. Cone terminals have many ribbon-style active zones at which second-order neurons receive input. We asked whether there are functionally significant differences in local Ca2+ influx among ribbons in individual cones. We combined confoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
(144 reference statements)
0
14
0
Order By: Relevance
“…Thus a single ganglion cell can pool the outputs of Ͼ10,000 photoreceptors as in the case of convergence of rods to ON alpha ganglion cells in the mammalian retina (76,340,373); clearly, heterogeneities in transmission at individual synapses will be averaged out by this circuit design. Nevertheless, Ca 2ϩ signals at individual ribbon synapses in cones have been found to vary strongly, which might help encoding contrasts over a wide range of light intensities (127).…”
Section: Role For Heterogeneity At Retinal Synapsesmentioning
confidence: 99%
“…Thus a single ganglion cell can pool the outputs of Ͼ10,000 photoreceptors as in the case of convergence of rods to ON alpha ganglion cells in the mammalian retina (76,340,373); clearly, heterogeneities in transmission at individual synapses will be averaged out by this circuit design. Nevertheless, Ca 2ϩ signals at individual ribbon synapses in cones have been found to vary strongly, which might help encoding contrasts over a wide range of light intensities (127).…”
Section: Role For Heterogeneity At Retinal Synapsesmentioning
confidence: 99%
“…The feedback signal measured in a cone is the sum of all the feedback signals from the various HCs received by that cone. That the feedback signal in cones is a mixture of inputs from various HCs was recently confirmed by Grassmeyer and Thoreson ( 2017 ) who showed that the various ribbons in a cone are affected differently when one modulates one HC. Polarizing only one HC leaves uncertain what the feedback signal from the other HCs is.…”
Section: Discussionmentioning
confidence: 72%
“…The Ca 2+ current (Figure 4a) could be partially blocked with 10 µM nifedipine and peaked around −20 mV, confirming that it was an L-type Ca 2+ channel. This was expected as cones in all other vertebrates studied express such Ca 2+ channels [58][59][60][61][62]. The presence of a functional cone I Ca in the cultured human retina is encouraging as Ca 2+ influx though these channels modulate the release of glutamate.…”
Section: Ion-channel Makeup Of Cones In Cultured Human Retinasmentioning
confidence: 79%